Bright light therapy accelerates the antidepressant effect of repetitive transcranial magnetic stimulation in treatment resistant depression: a pilot study. (2nd November 2021) - Barbini, Barbara; Attanasio, Francesco; Manfredi, Elena; Cavallini, Maria Cristina; Zanardi, Raffaella; Colombo, Cristina
Abstract: Objectives: We performed a randomized single-blinded study to assess the superiority of the combination strategy of repetitive Transcranial Magnetic Stimulation (rTMS) and Bright Light Therapy (BLT) over rTMS treatment alone in reducing depressive symptoms in treatment-resistant depression (TRD). Methods: We enrolled 80 inpatients with a diagnosis of TRD. All patients were randomly assigned into two groups: group A was treated with rTMS, compared to group B treated with a combination of rTMS and BLT. Depressive symptoms were weekly assessed (T0, T1, T2, T3) through the 17-item Hamilton depression rating scale (HDRS-17). Results: rANOVA (F=2.766, p=0.043) and post-hoc in HDRS-17 showed significant better scores in favour of group B every week (p<0.025, T1: 22.075 vs 17.200; T2: 16.100 vs 12.775; T3: 12.225 vs 8.900). Conclusions: The antidepressant effect of rTMS was enhanced and accelerated by its combination with BLT in treating resistant depression. KEYPOINTS: Almost one third of depressed patients does not respond to antidepressants; emerging neuromodulation and chronobiological techniques are effective antidepressant augmentation treatments. The aim of this study was to assess the superiority of the combination strategy of Light Therapy and TMS over TMS treatment alone in a group of treatment resistant depressed patients. The implication of this study in clinical practice is that a safe, low risk and cost-effective treatment, as Light Therapy, improves and accelerates the antidepressant effect of TMS.